2022
DOI: 10.1364/boe.455876
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive characterization of adult zebrafish models using Jones matrix optical coherence tomography

Abstract: The zebrafish is a valuable vertebrate animal model in pre-clinical cancer research. A Jones matrix optical coherence tomography (JM-OCT) prototype operating at 1310 nm and an intensity-based spectral-domain OCT setup at 840 nm were utilized to investigate adult wildtype and a tumor-developing zebrafish model. Various anatomical features were characterized based on their inherent scattering and polarization signature. A motorized translation stage in combination with the JM-OCT prototype enabled large field-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…1 c,j), probably due to the pigmentation. Furthermore, low DOPU values were observed in the bottom region of most images, which arise from multiple scattering at deeper tissue regions 36 .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…1 c,j), probably due to the pigmentation. Furthermore, low DOPU values were observed in the bottom region of most images, which arise from multiple scattering at deeper tissue regions 36 .…”
Section: Resultsmentioning
confidence: 96%
“…Literature has shown that healthy musculature in zebrafish exhibits increased birefringence values 33 . Further, a decrease in birefringence in diseased muscle tissue has been shown for murine and zebrafish models 36 , 38 , 39 .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations